Clinical Outcome Evaluation in Anterior Cruciate Ligament Reconstruction using Transportal Technique Augmented with Platelet Rich Plasma (PRP) Injection - Steesy Benedicta; Mouli Edward; Lukas Widhiyanto; Dwikora Novembri Utomo; Kukuh Dwiputra Hernugrahanto (The Hip and Knee Journal, 2020)
Background: Anterior cruciate ligament (ACL) injury is a common injury in the athlete with an incidence of 30-78 cases per year. PRP injection can be applied to enhance graft healing and help patient return to sports faster. Transportal placement is a newer technique and believed can handle this problem. No perspective surveillance system has been made to monitoring the outcome of ACL surgery using the transportal technique and PRP injection in our hospital.Materials and Methods: A total data of 157 patients using medical records in our hospital between 1 January 2014 and 31 December 2018 were evaluated. All patients underwent ACL reconstruction surgery using the transportal technique and additional platelet rich plasma (PRP) intraarticular, with the exclusion of multiple ligament and meniscal injuries. The values evaluated in this study were clinical examination, SF-12 Daily Living Score, Knee Injury and Osteoarthritis Outcome Score (KOOS), Oxford knee Score (OKS), Tegner Lysholm score and Cincinnati score. Patients were followed up from a minimum of 6 months to 4 years after surgery.Results: We found male-dominant (82.8%) patients with the mean age is 25.59 ± 7.61 years old. MOI mostly sports-related activity (78,9%). Anterior drawer and Lachman test post-surgery showed significant improvement. SF-12 showed increasing post-op with mean 80.94. Mean Tegner Lysholm and Cincinnati post-operative was 87.30 and 378.57. OKS pre and post-op mean was 23.56 and 43.82. No significant difference in KOOS score with p0.0001.Conclusions: The ACL reconstruction augmentation with PRP injection with the transportal technique showed significant satisfaction and function restored to normal.